2017
DOI: 10.1037/apl0000212
|View full text |Cite
|
Sign up to set email alerts
|

“Going out” of the box: Close intercultural friendships and romantic relationships spark creativity, workplace innovation, and entrepreneurship.

Abstract: The present research investigates whether close intercultural relationships promote creativity, workplace innovation, and entrepreneurship-outcomes vital to individual and organizational success. We triangulate on these questions with multiple methods (longitudinal, experimental, and field studies), diverse population samples (MBA students, employees, and professional repatriates), and both laboratory and real-world measures. Using a longitudinal design over a 10-month MBA program, Study 1 found that intercult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
54
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(62 citation statements)
references
References 76 publications
4
54
0
4
Order By: Relevance
“…In addition, social contagion between friends is particularly salient, providing a potential mechanism in which human energy can be transmitted through social interactions (Hatfield et al, 1994;Owens et al, 2016). For example, studies have shown that working alongside friends can engender happiness and positive affect (Sias and Cahill, 1998;Lu et al, 2017). Sense of meaning can also be derived from workplace friendship (Rawlins, 1992), and is closely related to energy (Fritz et al, 2011).…”
Section: Relational Energy As a Linking Pinmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, social contagion between friends is particularly salient, providing a potential mechanism in which human energy can be transmitted through social interactions (Hatfield et al, 1994;Owens et al, 2016). For example, studies have shown that working alongside friends can engender happiness and positive affect (Sias and Cahill, 1998;Lu et al, 2017). Sense of meaning can also be derived from workplace friendship (Rawlins, 1992), and is closely related to energy (Fritz et al, 2011).…”
Section: Relational Energy As a Linking Pinmentioning
confidence: 99%
“…Workplace friendship describes the quality of interpersonal relationship between individuals in the workplace where the relationship is characterized by mutual trust, commitment, reciprocal liking, and shared interests or values, which are driven by communal norms and socioemotional goals (Berman et al, 2002;Pillemer and Rothbard, 2018). Organizational research has found workplace friendship to have positive influences on both the employees and organization such as enhanced job significance , team-member exchange (Tse et al, 2008), well-being (Craig and Kuykendall, 2019), and innovation (Lu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…At the psychological level, the main benefits of globalization currently point to positive effects of global exposure on specific skills like creativity (Godart, Maddux, Shipilov, & Galinsky, 2015;Leung & Chiu, 2010;Leung, Maddux, Galinsky, & Chiu, 2008;Lu, Hafenbrack, et al, 2017;Maddux & Galinsky, 2009;Maddux, Hafenbrack, Tadmor, Bivolaru, & Galinsky, 2014;Tadmor, Galinsky, & Maddux, 2012). For example, research shows that people who have experience living or working in foreign countries are more creative than people without such experiences (Godart et al, 2015;Maddux & Galinsky, 2009).…”
Section: Effects Of Global Experience On Cognition and Behaviormentioning
confidence: 99%